Chemical assembling of amine functionalized boron nitride nanotubes onto polymeric nanofiber film for improving their thermal conductivity - Kim, Dukeun; Ha, Sumin; Choi, Hoi Kil; Yu, Jaesang; Kim, Yoong Ahm (ROYAL SOC CHEMISTRY, 2018)
The interfacial effect between an organic matrix and inorganic nanofillers on the thermal conductivity of a polymer composite was systematically explored by assembling amine-functionalized boron nitride nanotubes (BNNTs) onto an electrospun polyacrylic acid/polyvinyl alcohol nanofibrous web through either physical electrostatic interactions or chemical coupling reactions. The amine functionalization of BNNTs and their integration onto the electrospun nanofiber webs were confirmed by various analytical techniques. No distinctive change in thermal stability and conductivity could be observed between the pristine-and physically assembled polymeric nanofiber films; however, the chemically assembled nanofiber film produced via the chemical coupling reaction showed large improvements in both thermal stability and thermal conductivity. Our study demonstrated that it is possible to produce a highly thermally conductive polymer nanofiber film through interfacial engineering, even if the incorporation of inorganic filler is below 1 wt%.
Keywords: CARBON NANOTUBES; COMPOSITE FILMS; NANOCOMPOSITES; POLYETHYLENE; IMPROVEMENT; TRANSITION; NANOSHEETS; INTERFACE; PALLADIUM; ALUMINA